Tahap perkembangan afektif anak sekolah dasar : Tahap perkembangan afektif anak sekolah dasar - NurAyu Winingsih; Hariyanto S. Auna (LPPM UNiversitas Bina Mandiri Gorontalo, 2023)
A person's life is generally full of encouragement and interest to achieve or have something. How many drives and interests he has is the basis of his emotional experience. The journey of one's life is not the same. Different desires and interests are owned by each individual according to their respective lifestyles. Students are human beings with all their nature. They have feelings and thoughts and desires or aspirations. They have basic needs that need to be met (food, clothing, shelter), the need for security, the need for recognition, and the need to actualize themselves (to be themselves according to their potential). The relationship between emotions and values, morals and attitudes is that emotional impulses can affect one's thoughts and behavior. Therefore, an individual in responding to something is more directed by reasoning and objective considerations.